Preoperative MRI evaluation of lesion–nipple distance in breast cancer patients: thresholds for predicting occult nipple–areola complex involvement. Issue 8 (August 2018) - Mariscotti, G.; Durando, M.; Houssami, N.; Berzovini, C.M.; Esposito, F.; Fasciano, M.; Campanino, P.P.; Bosco, D.; Bussone, R.; Ala, A.; Castellano, I.; Sapino, A.; et al.
Abstract : Aim: To identify clinically occult nipple–areola complex (NAC) involvement using preoperative magnetic resonance imaging (MRI), to inform selection of patients eligible for nipple-sparing mastectomy (NSM) or skin-sparing mastectomy (SSM). Material and methods: This was a retrospective study of 195 patients, who had preoperative breast MRI (February 2011 to January 2017) before undergoing surgical treatments (NSM or SSM) for newly diagnosed breast cancer. Tumour features at MRI (mass or non-mass lesion, diameter, lesion–NAC distance [LND]) and pathology (lesion diameter, histopathological type, receptor status) were recorded, as well as the type of surgery (NSM/SSM) and presence (NAC+) or absence (NAC–) of tumour at intraoperative evaluation of retroareolar tissue. Mann–Whitney test, Fisher's exact test, logistic regression, and receiver operating characteristic (ROC) curve analysis were used for analysis of NAC+ versus NAC– to assess variables that predict NAC tumoural involvement. Results: Over the study period, NAC+ was proven histologically in 71/200 (35.5%) surgical treatments, while there were 129/200 NAC– (72 NSM and 128 SSM performed). LND at MRI was statistically ( p <0.001) lower in NAC+ patients than in NAC– patients. The area under the ROC curve (0.82, 95% confidence interval [CI]: 0.76–0.88) indicated 10 mm as the best cut-off, with sensitivity of 82%, specificity of 72%, and accuracy of 79%. A 5-mm cut-off enhanced sensitivity, whereas a 15-mm cut-off favoured specificity. Conclusions: MRI is a useful tool for identifying NAC+ patients; a 10-mm cut-off for LND assists selection of patients for NSM, although intraoperative retroareolar tissue examination remains mandatory. Highlights: MRI is a useful tool for identifying patients with NAC tumoural involvement. The discriminating ability of Lesion-to-Nipple distance was good by ROC analysis. Lesion-to-Nipple distance between 5 and 15 mm allows the selection of patients suitable for NSM. Intraoperative retroareolar tissue examination remains mandatory.